Stereological analysis of size and density of hepatocytes in the porcine liver. Issue 4 (29th December 2016) - Junatas, Khan L.; Tonar, Zbyněk; Kubíková, Tereza; Liška, Václav; Pálek, Richard; Mik, Patrik; Králíčková, Milena; Witter, Kirsti
Abstract: The porcine liver is frequently used as a large animal model for verification of surgical techniques, as well as experimental therapies. Often, a histological evaluation is required that include measurements of the size, nuclearity or density of hepatocytes. Our aims were to assess the mean number‐weighted volume of hepatocytes, the numerical density of hepatocytes, and the fraction of binuclear hepatocytes (BnHEP) in the porcine liver, and compare the distribution of these parameters among hepatic lobes and macroscopic regions of interest (ROIs) with different positions related to the liver vasculature. Using disector and nucleator as design‐based stereological methods, the morphometry of hepatocytes was quantified in seven healthy piglets. The samples were obtained from all six hepatic lobes and three ROIs (peripheral, paracaval and paraportal) within each lobe. Histological sections (thickness 16 μm) of formalin‐fixed paraffin‐embedded material were stained with the periodic acid‐Schiff reaction to indicate the cell outlines and were assessed in a series of 3‐μm‐thick optical sections. The mean number‐weighted volume of mononuclear hepatocytes (MnHEP) in all samples was 3670 ± 805 μm 3 (mean ± SD). The mean number‐weighted volume of BnHEP was 7050 ± 2550 μm 3 . The fraction of BnHEP was 4 ± 2%. The numerical density of all hepatocytes was 146 997 ± 15 738 cells mm −3 of liver parenchyma. The porcine hepatic lobes contained hepatocytes of a comparable size, nuclearity and density. No significant differences were identified between the lobes. The peripheral ROIs of the hepatic lobes contained the largest MnHEP with the smallest numerical density. The distribution of a larger MnHEP was correlated with a larger volume of BnHEP and a smaller numerical density of all hepatocytes. Practical recommendations for designing studies that involve stereological evaluations of the size, nuclearity and density of hepatocytes in porcine liver are provided.